Efficient analysis of MIMO-OFDM system in Nakagami-m fading channel - Ho, Van-Cuu; Le, Hoang-Hiep; Thi Nguyen, Thu-Hang (Vietnam Journal of Science and Technology, 2016)
Bit error rate (BER) and symbol error rate (SER) performance response fading parameter for multiple-input multiple-output (MIMO) orthogonal frequency division multiplexing (OFDM) system over Nakagami-m fading channel would be provided in this study. Some channel simulations and evaluations were for 2×2 MIMO-OFDM system in which data are sent from two transmit antennas to two receive antennas. In this study, authors have used binary phase-shift keying (BPSK) and quadrature phase-shift keying (QPSK) modulation techniques to modulate the data stream. In addition, numerical results have been presented and compared for several different environmental propagations such as Nakagami-m, Rician, Rayleigh multipath fading channels, and non-fading additive white Gaussian noise (AWGN) channel. Based on such obtained presentation and comparison, the paper would discuss further about relation between value of paramater m and quality of system.